Detection of DNA sequence variation in cellulose synthase (CesA1) gene from shorea parvifolia ssp. parvifolia - Teo, Chiew Phin (Universiti Malaysia Sarawak, UNIMAS, 2010)
Shorea parvifolia ssp. parvifolia is belongs to the Dipterocarpaceae family which constitutes the major valuable timber in the tropical forest of Asia. The resistance and hard wood properties of this species are mainly contributed by the formation of secondary cell wall made up by a large portion of cellulose. Wood consists of 40 to 50 % of cellulose and the percentage varies among species and within species. This variation can be detected and it enables the selection of desired wood properties. In this study, Cleaved Amplified Polymorphic Sequence (CAPS) technique was used to detect and verify the 2 SNP sites detected in cellulose synthase (CesA1) gene which is responsible in encoding the cellulose material in12 S. parvifolia ssp. parvifolia samples. Primer SPPT3-F and SPPT3-R were used to amplify the 802 bp CesA1 gene prior to restriction enzyme (EcoRI and EarI) digestion. As EcoRI cutting site was presented in all of the 12 samples, it shows that no mutation was occurred at the SNP site detected at nucleotide number 376 in the 802 bp CesA1 gene. On the other hand, the partial CesA1 gene from all of the 12 samples was not restricted by the EarI. Due to the absence of positive control and the possibility of non optimal reaction condition and the inactivity of restriction ezyme, the mutation occurred at the SNP site detected at nucleotide number 58 cannot be confirmed in this study. Although both of the SNPs detected in previous study cannot be verified in this study, the CAPS technique showed cost effectiveness and the result can be obtained in shorter period.